Keeping faith in Congress : why persistence, compassion, and teamwork will save our democracy - Capps, Lois (Fortress Press, 2018)
In 1996, Walter Capps won a seat in Congress. Months later, he suffered a massive heart attack and died in his wife's arms. Lois Capps decided to run for her husband's seat. She won that election and went on to serve six more terms in Congress. Now, Lois Capps poignantly tells her story. No matter what personal or professional obstacles she faced, she never lost faith in democracy. She shares the lessons she learned, hoping that others can be inspired to work on behalf of the common good.